Screening of protease and lipase sources from visceral organs of Euthynnusaffinis - Mardina, Vivi; Harmawan, Tisna; ,, Fitriani; Hildayani, Goldha Maulla; Yusof, Faridah (Institute of Physics Publishing, 2018)
Euthynnusaffinis is one of tuna species that distributed throughout the world. Their visceral accounts for approximate less than 20% of body weight and its value are still underutilized. This study screened four the potential individual visceral organ to produce protease and lipase enzyme viz. spleen, stomach, pancreas, and liver. Among the individual visceral organ, liver exhibited the highest source for protease activity (57.786 U/ml), while pancreas revealed as the best source for lipase activity (69.425 U/ml). Therefore, the finding of alternative sources for protease and lipase in this study might converted visceral waste by product to generate protease and lipase enzyme that may be applied in biotechnological process.